The effect of educational level and economic growth on poverty in mandailing natal - Zainal Arifin (Proceedings of AICS - Social Sciences, 2017)
The purpose of this paper is to find out the influence of educational level and economic growth on poverty level in Mandailing Natal. This study used a multiple linear regression analysis. The data used are annual data from 2009 until 2013, the results of the regression analysis showed that the level of education and economic growth to the level of poverty in Mandailing Natal.